Philippine macroeconomic issues and their causes - Gerardo P. Sicat (University of the Philippines, School of Economics (UPSE), 2006)
Philippine economic growth is below the typical performance of East Asian neighbors. GNP is outstripping GDP as a result of national labor income arising from work in other economies and relatively slow domestic output growth. Instead of high domestic investments fueling the absorption of labor at home at good wages, labor seeks migration to other countries with labor shortage and high employment rates. Domestic output is growing with a rising services component at the expense of industry and agriculture. High domestic labor standards make labor unit costs high and the inadequate growth of capital investment opportunities keep productivity relatively low. Capital investment policies - despite economic liberalization that made possible a growing industrial export sector - continue to restrict foreign investments in critical sectors that are prohibited in the Constitution that can be traced to 1935 provisions. National saving rates are low relative to investment needs, especially in highly needed infrastructure and public utilities - areas in which restrictions to foreign direct investment are binding. These saving rates are also low compared to those experienced in East Asian neighbors. The fiscal sector has been a major cause of poor national saving because of persistent current budgetary deficits. External trade and payments positions have improved as a result of economic liberalization. But the full potentials of the economy can be extended with reforms affecting resource use, including labor and capital markets. The potentials for development in the Philippines are not fully exploited at home so that the conquest of poverty is slow. A relative indication of this underperformance can be derived from the immense improvement of economic fundamentals from poor to improving in 2006 just as soon as the government was able to reform the fiscal front.
Keywords: 330